TUGAS DAN WEWENANG DPRD DALAM PENGAWASAN PELAKSANAAN APBD DI KABUPATEN BEKASI JURNAL ILMIAH - Fajar Bayu Suseto , Untung Dwi Hananto *), Ratna Herawati (Diponegoro Law Journal, 2013)
Monitoring functions Bekasi Regency Council is one of the three functions of the Council in addition to the legislation and budget functions.  Monitoring functions more  focused  on  the  function  of  Parliament  in  monitoring  local  regulation  and Budget  (APBD).  In  performing  this  function,  the  Council  collaborates  with  the regents in conducting the discussion. Approved or not a draft budget in the future is a decision of the Council it self. Duties  and  powers  of  Council  in  monitoring  the  implementation  of  the  Bekasi Regency,  regulated  in  Bekasi  Council  Regulation  No.  1  of  2010  about  Bekasi Regency Council rule’s in controlling the budget is not only limited to the aspects ofthe use of funds, but also on the income and revenue.  And monitoring performed by Council  not  only  to  the  Council  budget,  but  also  the  implementation  of  local regulation and decree. From the implementation of the monitoring function, it can be seen clearly the impact of the delivery of local government and regional development. All that perform supervisory duties is a commission by the commission fields each. The internal barriers about monitoring of management factors in Bekasi budget are education,  experience,  human  resources  regulations   and  programs,  while  the external  resistance  is  change  legislation,  recruitment  of  political  parties,  public participation and the media.